2022
DOI: 10.1007/s11145-022-10321-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of context and discrepancy when reading multiple documents

Abstract: On a daily basis, most people read about issues of interest from a diversity of sources. Moreover, the information they encounter frequently encompass discrepancies, ranging from minor inconsistencies to straight contradictions. Readers may construct coherent representations from discrepant contents by linking contents to their respective sources and connecting the sources with agree-disagree or other types of connectives. Across research studies, however, college-level readers' attention to sources has been f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 48 publications
(112 reference statements)
2
12
0
Order By: Relevance
“…Our findings complement prior findings on external context effects when reading and writing about multiple documents (Schoor et al, 2023). Schoor et al (2023) found that in a university context, students more often compared texts with each other, used adversative connectors and addressed the discrepancy between texts in an essay. Thus, they consider it more important to convey a complete and accurate picture, in terms of theory: a documents model (e.g., Britt & Rouet, 2012).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Our findings complement prior findings on external context effects when reading and writing about multiple documents (Schoor et al, 2023). Schoor et al (2023) found that in a university context, students more often compared texts with each other, used adversative connectors and addressed the discrepancy between texts in an essay. Thus, they consider it more important to convey a complete and accurate picture, in terms of theory: a documents model (e.g., Britt & Rouet, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…In the prior study, the participants were provided with two documents per target topic and had to actually write an overview essay based on a question that allegedly either their professor or their best friend asked them. In the present study, we focused on the selection stage of the information seeking process and provided the participants with the introductory question in the same way as in Schoor et al (2023), but asked them to select documents for further reading. Of the eight target topics in the Schoor et al (2023) study, we selected only four due to time constraints.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations